Ischemia-reperfusion histopathology alterations of the rabbit intestinal wall with and without ischemic preconditioning - Gomes,Otoni Moreira (2011)
PURPOSE: To evaluate the histopathology alterations of the intestinal mucosa of rabbits submitted to mesenteric artery ischemia and reperfusion with and without ischemic preconditioning. METHODS: Two groups of ten male New Zealand white rabbits body (weight 2.2-3.0, average 2.5 kg). For mesenteric ischemia induction in all animals the small bowel and mesentery were cut 30cm and 60cm far from the gastroduodenal pyloric transition before the proximal mesenteric artery occlusion. In the Group 1 animals, the proximal mesenteric artery was occluded for 45 min with an atraumatic vascular clamp, followed by reperfusion for 30 min. In the Group 2 the 45 min ischemic phase was preceded by three cycles of ischemia (2 minutes each) alternated with three cycles of reperfusion (2 minutes each). For istopathology study small bowel biopsies were obtained before ischemia (control), after 45 min of mesenteric ischemia and at 30 min. of mesenteric artery reperfusion. RESULTS: In the Group I animals, the followings histopathology grade results were observed: t1, mean 2,8; t2, mean 3,3. Using the Kruskal-Wallis non-parameter test, differences between t0 and t1 and t0 and t2 were significants (p<0.05), but not significant between t1 and t2 (p>0.05). In the Group 2 animals histopathology grade results were: t1 mean 2,6 and t2, mean 2,1. Differences between t0 and t1, t0 and t2 were significant (p<0.05). It was not observed differences (p>0.05) between results of t1 in both groups but histopathology injury observed in Group 1 t2 biopsies were higher (p<0.05) than observed in the same period (t2) of Group 2 animals. CONCLUSION: Microscopic examination of the biopsies revealed significant evidence of preconditioning protection against small bowel wall ischemia-reperfusion injury.